INFLUENCE OF SENSORY MARKETING ELEMENTS ON CONSUMER BEHAVIOR - Evtimova, P (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The purpose of this article is to present the impact of elements of sensory marketing on consumer behavior. To achieve this goal, the article seeks answers to the following questions: What is sensory marketing? What is the difference between traditional marketing and sensory marketing? Which are the elements of sensory marketing and what is their role? How to use the sensory elements separately and how to use them in an integrated way to provoke a desired behavioral response? What is multisensory branding and how to apply it successfully? How to use the elements of sensory marketing to successfully achieve brand differentiation?